Peripheral clock disruption and metabolic disease: moving beyond the anatomy to a functional approach - Marino, Gabriella M.; Arble, Deanna M. (Frontiers in Endocrinology, 2023)
Sleep and circadian disruption are associated with an increased risk of metabolic disease, including obesity and diabetes. Mounting evidence indicates that misaligned and/or non-functional clock proteins in peripheral tissues critically contribute to the presentation of metabolic disease. Many of the foundational studies which led to this conclusion have focused on specific tissues such as the adipose, pancreas, muscle, and liver. While these studies have greatly advanced the field, the use of anatomical markers to manipulate tissue-specific molecular clocks may not be representative of the circadian disruption that occurs within the clinical population. In this manuscript, we argue that investigators can gain a better understanding of the consequences of sleep and circadian disruption by targeting groups of cells with a functional relationship, even if those cells go beyond anatomical boundaries. This approach is especially important when considering metabolic outcomes which rely on endocrine signaling molecules, such as leptin, that have multiple sites of action. Through the review of several studies, as well as our own work, this article reframes peripheral clock disruption from a functional approach. We additionally present new evidence that disruption of the molecular clock within all cells expressing the leptin receptor affects leptin sensitivity in a time-dependent manner. Taken together, this perspective aims to provide new insight into the mechanisms leading to metabolic disease associated with circadian disruption and various sleep disorders.